STRATEGI PENINGKATAN KEPATUHAN MEMBAYAR PAJAK MELALUI PENINGKATAN KUALITAS PELAYANAN DAN PENDEKATAN KEARIFAN LOKAL - Mariti, Mariati; Afrian, Dicky; Magdalena, Cecilia; Sitio, Astri Bonita (Jurnal Pendidikan Ekonomi, 2023)
This study aims to identify the concept of quality of services and local wisdom in an effort to increase tax payments. This research is carried out using the study method of the literature review from various kinds of primary and secondary data sources, literature, and the results of the research studies that have existed previously relevant. The results of this study show satisfaction against services provided to the community will increase taxpayer compliance to fulfill its tax obligations, as well as local wisdom values available on the community can be adopted into an increased strategy of paying tax obedience. The quality of the services provided properly, can have an impact on providing a satisfied attitude for taxpayers and will eventually increase public obedience to provide tax obligations. In addition, the application of local wisdom that has been attached to society is also needed by the role of elements from the community itself in the form of indigenous figures or people who can collaborate with the government to increase compliance to pay taxes.